Garfield (2012), volume 5 ebook - Davis, Jim (Garfield (2012), 2015)
Because you can never have too much of a good thing, here's the next collection of Garfield's comic book adventures. This volume follows the Fat Cat as he gets caught in a time warp, battles monsters both in the forest and under the bed, and faces two of his greatest foes: the Calzone Creature and Zombie Meatballs! Collects issues #17-20.